Synchronization of sanctions between Ukraine and the European Union - Baklanova, K. V.; Myronov, O. D.; Yakoviyk, I. V. (Аналітично-порівняльне правознавство, 2025)
The article presents a comprehensive study of the process of synchronizing Ukraine’s sanctions policy with the European Union’s legal mechanisms. In the context of the Russian Federation’s armed aggression and Ukraine’s strategic course toward European integration, the issue of harmonizing restrictive measures with the EU sanctions regime has gained particular relevance. The authors analyze the legal basis for Ukraine’s cooperation with the EU in the field of foreign and security policy, particularly the provisions of the Association Agreement that establish the framework for coordinating sanction approaches. The article examines key stages in the adaptation of Ukrainian sanctions legislation, particularly the Law of Ukraine “On Sanctions,” the decision-making practices of the National Security and Defense Council of Ukraine, and Ukraine’s involvement in the development of sanctions lists aligned with European counterparts. The focus is on examples of effective synchronization of Ukrainian restrictive measures with EU sanctions, especially with respect to individuals promoting the Russian Federation’s aggressive policies. At the same time, the article highlights that Ukraine retains autonomy in decision-making by conducting its own assessment of the appropriateness of sanctions. Special attention is given to prospects for improving the legal mechanism for sanctions implementation, including proposals for the adoption of a special law that would enable the simplified transposition of EU sanctions, provided they comply with national interests and legal standards. The article outlines current trends in the development of Ukraine’s sanctions legislation, including the introduction of criminal liability for the deliberate circumvention of sanctions, legislative amendments to combat the re-export of prohibited goods, and Ukraine’s integration into the European sanctions control framework. It also analyzes the impact of recent EU initiatives—particularly the anti-circumvention instrument—on shaping Ukraine’s corresponding policy. The importance of strengthening cooperation within the framework of the Ukraine–EU Joint Security Commitments and Ukraine’s potential participation in the EU’s Common Foreign and Security Policy sanctions-making process is emphasized. As a result of the study, the authors conclude that effective synchronization of sanctions policy with the European Union is not only a means of strengthening national security, but also an important element of Ukraine’s legal integration into the EU. Current legislative initiatives, backed by political will and international coordination, are forming the basis for a coherent and effective sanctions policy capable of addressing the challenges of today’s geopolitical landscape and reinforcing Ukraine’s position as a full-fledged participant in the European security system.